Dental Notation System Used in Dental Teaching in Different Dental Collages - Huda Aljalali; Huda Elmehadwi; Huda Mohamed (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this study was to find the most commonly used Tooth Numbering System to teach and learn in dental collages in various universities (Benghazi University, Omar Mukhtar University and Libyan International Medical University) by both academic staff and fourth year dental students, to identify the most commonly taught TNS in different dental colleges, to understand the reason why dental staff prefer to use a specific TNS, and the consequences of using more than one TNS. This cross-sectional study was conducted within the dental collages of various Medical Universities. The questionnaire containing 11 questions was randomly distributed to 120 individuals (60 deans of academic staff and 50 fourth year dental students). The palmer notation system was the most commonly used to teach and learn by academic staff and dental students in teaching and practiced in dental collages, while the universal notation system was the least used to teach and learn by academic staff and dental students. As well as the most TNS preferred to use by academic staff and dental students in operative, oral surgery departments and orthodontic department in academic teaching was the palmer notation system while the least TNS use was universal notation system. The Palmer TNS proved to be the most taught TNS in dental colleges in different University. It is advised that the Palmer TNS be implemented as a unified system in my country, due to the advantages of this particular TNS and the benefits of using one single TNS. هدفت هذه الدراسة الي العثور علي نظام ترقبم الاسنان الأكثر تعاملا في تدريس في مختلف كليات الاسنان في جامعة بنغازي وجامعة عمر المختار و جامعة الدولية للعلوم الطبية من قبل أعضاء هيئة التدريس و طلاب الاسنان في السنة الرابعة ولفهم السبب الذي يجعل أعضاء هيئة التدريس يقضل استخدام نظام ترقيم واحد و عواقب استخدام اكثر من نظام ترقيم واحد . المواد و الطريقة: أجريت هذه الدراسة المقطعية داخل كليات الاسنان في مختلف الجامعات الطبية و تم توزيع الاستبيان الذي يحتوي علي 11 سؤالا بشكل عشوائى علي 120 فرد (60 أعضاء هيئة التدريس و 50 طالبا في السنة الرابعة)ز النتائج: كان نظام التدوين بالمر هو الأكثر استخداما لتدريس و التعلم من قبل أعضاء هيئة التدريس و طلاب طب الاسنان , في حين كان نظام التدوين العالمي هو الأقل استخداماللتدريس و التعلم من قبل أعضاء هيئة التدريس و طلبة السنة الرابعة.و كان النظام الأكثر استعمالا في قسم جراحة الفم و التقويم و الحشو هو نظام بالمر بينما الأقل استخداما هو نظام التدوين العالميز الاستنتاج: اثبت نظام بالمر انه النظام الأكثر شيوعا في التدريس في مختلف كليات الاسنان في الجامعات الطبية و ينصح بتنفيذ نظام بالمر كنظام موحد في مختلف كليات نظرا لمزايا هذا النظام و فوائد استخدامه.